A rare case of neomercazole induced hepatitis - Varma, Muralidhar; Mansingh, Jaikaran; Sivakumar, Devyani; Dhalla, Rabia; Vidyasagar, Sudha; B., Nandakrishna (International Journal of Research in Medical Sciences, 2018)
Neomercazole is one of the most commonly used drugs to treat hyperthyroidism. Common side effects include rash, hair loss and agranulocytosis. Hepatotoxicity is a common side effect of Propylthiouracil, the other major antithyroid drug, but it has been rarely described as a side effect of neomercazole. Here, a patient presents with hepatitis 6 months after starting neomercazole therapy for graves disease. Diagnosis is based on excluding other causes of hepatitis, and treatment involves removing the offending drug. This is followed by normalization of liver function. Rechallenging should not be done as it can lead to recurrence of symptoms.